2020
DOI: 10.1111/jvim.16008
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25‐hydroxyvitamin D concentration and infectious respiratory disease complex in shelter dogs

Abstract: Background: Hypovitaminosis D is a risk factor for the development of respiratory infections in humans and repletion can be protective. Objectives: Determine if serum 25-hydroxyvitamin (OH)D concentrations are lower in shelter dogs and if 25(OH)D concentrations are associated with clinical signs of canine infectious respiratory disease complex (CIRDC) or with time in the shelter. Animals: One hundred forty-six shelter dogs (clinically ill n = 36, apparently healthy n = 110) and 23 nonshelter control dogs. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…There is considerable controversy regarding the best means to assess and interpret autoagglutination in dogs, and when noted, whether a DAT could and should still be performed [ 3 , 4 , 6 , 20 ]. As expected, more DAT+ samples agglutinated than did DAT- samples in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is considerable controversy regarding the best means to assess and interpret autoagglutination in dogs, and when noted, whether a DAT could and should still be performed [ 3 , 4 , 6 , 20 ]. As expected, more DAT+ samples agglutinated than did DAT- samples in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…While the SAT is recommended by the ACVIM consensus statement [ 6 ], we had questioned its value in the past [ 1 , 5 ]. A recent study also suggested that a SAT using a 1:1 and 1:4 blood to phosphate-buffered saline dilution with microscopic evaluation was not a useful diagnostic test for IMHA in dogs [ 20 ]. However, the diagnostic accuracy of a 1:49 dilution SAT with microscopic evaluation was much higher, which was attributed to a reduction in non-specific agglutination as happens with saline washing of RBCs [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations